Proyecto de factibilidad para la implementación de una empresa productora de melcochas a base de miel de caña de azúcar en la ciudad de Gualaquiza y su comercialización en la ciudad de Loja - Chuva Buele, Diana Paola (2023)
TheThe valuation of investment projects has had a significant boom due to the uncertainty of investors, due to having a certain degree of insecurity when investing their money; In this context, the present research work had the objective of carrying out a feasibility project for the implementation of a company that produces marshmallows based on sugar cane honey in Gualaquiza City and its commercialization in Loja City, based on the market, technical, administrative and legal, economic-financial studies. The research has a qualitative and quantitative non-experimental approach, it is exploratory in nature, for which research methods, techniques and instruments were used that allowed the collection, organization, presentation, analysis and interpretation of information obtained. The study population was 144,065 men and women from 16 to 60 years old, from which a sample of 384 surveys was calculated. The market study determined an unsatisfied demand of 46,838,941 grams of marshmallow. The location of the plant Will be in the city of Gualaquiza. An installed capacity of 14,164,800 grams of marshmallow was determined, which takes advantage of 100% of the capacity used, with this a market share of 30.24% was obtained; The implementation of the project will generate 7 sources of work. In the administrative and legal study it was determined that the company will be established as a Limited Liability company. The initial investment of USD 42,600 American dollars. A Net Present Value (VAN) of USD 93,321.53 was determined, being a positive value, exceeding the initial investment; the Internal Rate of Return (IRR) of 87,27%; in relation to the Capital Recovery Period (P.R.C) it will be in 1 years, 4 months and 20 days; in the Cost/Benefit Ratio (RCB) there was a return of 0.40 cents; in the Sensitivity Analysis (AS) it was obtained that the project can support up to an increase in its costs of 19.80%; and a decrease in income up to 13.92%. It is concluded that according to the results obtained in the different studies, the project is viable, so investors are recommended to consider this proposal.